Molecular Simulations of the Hydration Behavior of a Zwitterion Brush Array and Its Antifouling Property in an Aqueous Environment - Xiang, Yuan (Langmuir : the ACS journal of surfaces and colloids, 2018)
We carried out umbrella sampling and molecular dynamics (MD) simulations to investigate molecular interactions between sulfobetaine zwitterions or between sulfobetaine brushes in different media. Simulation results show that it is more energetically favorable for the two sulfobetaine zwitterions or brushes to be fully hydrated in aqueous solutions than in vacuum where strong ion pairs are formed. Structural properties of the hydrated sulfobetaine brush array and its antifouling behavior against a foulant gel are subsequently studied through steered MD simulations. We find that sulfobetaine brush arrays with different grafting densities have different structures and antifouling mechanisms. At a comparably higher grafting density, the sulfobetaine brush array exhibits a more organized structure which can hold a tightly bound hydration water layer at the interface. Compression of this hydration layer results in a strong repulsive force. However, at a comparably lower grafting density, the brush array exhibits a randomly oriented structure in which the antifouling of the brush array is through the deformation of the sulfobetaine branches